Kritik Atas Kesenjengan Sosial Dalam Lagu ”Negri Ngeri” Karya Marjinal - Bagus Septiyanto Firdaus; Khamdan Syakuro (Simpati, 2023)
The song "Negri-Ngeri" by Marginal is a piece of music that contains a social message and criticism of injustice and difficult life in the country of Indonesia. The lyrics reflect the external reality faced by today's society and created this song based on the current state of society, so that the external reality can clarify the meaning contained in the lyrics. In the past, this song seemed exaggerated and underestimated for some people with the opinion "punk kids don't need government criticism because of their life on the streets and just nonsense" but in fact the song is relevant to the current situation. The band of this song dared to make lyrics that were frontal and offensive to the government, even though the marginal band whose musical background was punk and punk children was just nonsense because of their idealists who lived on the streets and were grumbled, but it turned out to be very relevant to the current situation. In this case, music becomes one of the effective media to convey messages to the general audience. The language used in the song is Indonesian, which is the official language of Indonesia. Marjinal made this song with the aim to voice their dissatisfaction with the state of the country and provide a reminder to the Indonesian people that change needs to be made. The song "Negri Ngeri" is one example of a musical work that can inspire and have a positive influence on society, especially for those who feel marginalized or underappreciated in the existing socio-political system. The result of this study is that we can understand the intention of marginal to make social criticism songs to convey the message so that social people know that there are injustices made by the ruler. The method used in this article is qualitative and describes the content of youtube content.